Affiliate Marketing: Marketing Strategy to Increase Online Sales - Popo Suryana (Journal Arbitrase : Economy, Management and Accounting, 2023)
With the rapid growth of e-commerce and digital marketing trends, a deep understanding of how Affiliate Marketing can be an effective tool in optimizing online sales has become very important. This research aims to identify, analyze and evaluate the effectiveness of marketing strategies through Affiliate Marketing in increasing online product or service sales. This research uses a qualitative approach with descriptive methods. The research results show that effective implementation of affiliate marketing strategies can increase a company's online sales. Selection of the right affiliate, attractive incentive offers, and effective communication between the company and affiliates are the main factors in achieving success. Quality and creative content, as well as optimization of user experience on websites, play an important role in attracting consumer attention and increasing conversion rates. Proper market segmentation provides a clear focus, while renewal and innovation are key in maintaining competitiveness in a dynamic digital environment. Thus, the research results provide practical guidance for companies in developing and improving their affiliate marketing strategies to achieve online sales goals more effectively.